Consequences of COVID-19 on children’s learning and their responses - Maharjan, Shyam Krishna; Devkota, Bhimsen (Journal of Health Promotion, 2022)
This article briefly highlights the effects of COVID-19 on schoolchildren’s learning and their needs. The global COVID-19 pandemic has had a detrimental effect on the education system, among others. Lockdowns and school closures during COVID-19 reduced children’s learning opportunities, leading to a long-term impact on their ability to learn. The learning loss is yet to be known as the world is still suffering from the virus and its variants. Teachers have struggled to complete the course and students were under pressure to study many lessons in a short window of time in order to make up for the school time lost during the pandemic. Because of vaccination including the booster dose against COVID-19, in addition to other preventive and control measures adopted by the public, the prevalence of COVID-19 has reduced. The government of Nepal and other stakeholders have made a decision to reopen schools and continue facilitating student learning face-to-face and through alternative teaching-learning approaches, ensuring health promoting school.